Integral kidney function assessment in pediatric patients with glycogen storage diseases - Reyes-Apodaca, Magali; Consuelo-Sánchez, Alejandra; Vázquez-Frias, Rodrigo; Rodríguez-Espino, Benjamín Antonio; Medeiros, Mara (Frontiers in Pediatrics, 2025)
IntroductionGlycogen storage diseases (GSDs) are a group of hereditary metabolic disorders with variable clinical manifestations, depending on the enzyme and organ affected. Renal dysfunction, including hyperfiltration, proteinuria, and renal tubular acidosis (RTA), is a known complication, particularly in GSD types of Ia and Ib.MethodsThis cross-sectional study evaluated renal function in 17 pediatric patients with different GSD types using an integral kidney assessment (IKA). The comprehensive evaluation included biochemical and urinary analyses, glomerular filtration rate calculations, and acidification tests.ResultsThe median age at first renal evaluation was 33 months, and nutritional management was often suboptimal at this stage. Through IKA, renal alterations were identified in 47% of the patients. Hyperfiltration was present in 40% of GSD type I patients, while lactic acidosis was noted in 30% of these cases. Two siblings with GSD XI presented with proximal RTA and Fanconi syndrome, highlighting severe tubular involvement. Distal RTA was documented in one non-adherent GSD Ia patient, underscoring the importance of metabolic control.DiscussionThis study emphasizes the heterogeneity of renal manifestations among different GSD subtypes. Hyperfiltration, particularly in GSD I, may result from altered energy metabolism and compensatory mechanisms within the renal tubules. Proximal tubular damage in GSD XI reflects glycogen and monosaccharide accumulation within renal epithelial cells. Adherence to dietary and medical interventions is critical for mitigating renal complications and ensuring growth and development in GSD patients. Annual kidney evaluations are recommended for early detection of renal dysfunction, enabling timely initiation of therapeutic strategies such as alkali therapy and angiotensin-converting enzyme inhibitors.